Review of Recent Offshore Floating Photovoltaic Systems - Gang Liu; Jiamin Guo; Huanghua Peng; Huan Ping; Qiang Ma (Journal of Marine Science and Engineering)
Photovoltaic (PV) power generation is a form of clean, renewable, and distributed energy that has become a hot topic in the global energy field. Compared to terrestrial solar PV systems, floating photovoltaic (FPV) systems have gained great interest due to their advantages in conserving land resources, optimizing light utilization, and slowing water evaporation. This paper provides a comprehensive overview of recent advancements in the research and application of FPV systems. First, the main components of FPV systems and their advantages as well as disadvantages are analyzed in detail. Furthermore, the research and practical applications of offshore FPV systems, including rigid floating structures and flexible floating structures, are discussed. Finally, the challenges of offshore FPV systems are analyzed in terms of their stability and economic performance. By summarizing current research on FPV systems, this overview aims to serve as a valuable resource for the development of offshore FPV systems.